Respon Fisiologis Kedelai [Glycine max (L.) Merr.]Varietas Grobogan terhadap Tingkat Naungan yang Berbeda - Bestari, Andini Vermita; Darmanti, Sri; Parman, Sarjana (Biospecies, 2018)
The study aimed to analyze physiological responses of soybean varieties Grobogan to different shade levels, including changes in amount of leaf total protein content, photosynthetic pigments content, index stomata and stomata gap width and vegetative growth. The research was conducted using a Completely Randomized Design (CRD) one factor, that is shading level with three treatments: no shading, 50% shade and 70% shade. Data were analyzed by ANOVA and continued by DMRT at 95% confidence level. The results showed that Soybean varieties Grobogan is able to adapt and survive under 50% and 70% shade. Varieties Grobogan responded to increased shade by increasing leaf total protein content and photosynthetic pigments content and decreasing index stomata and stomatal gap width. Shaded plants showing stunted vegetative growth, seen by decreased of leaf number, leaf area, leaf thickness, stem height, stem diameter, root length and plant weight.